Robustness of egg production methods as a fishery independent alternative to assess the Eastern Baltic cod stock (Gadus morhua callarias L.) - Kraus, Gerd; Hinrichsen, Hans-Harald; Voss, Rüdiger; Teschner, Eske; Tomkiewicz, Jonna; Köster, Friedrich-W. (2012)
At present, several cod stocks are outside safe biological limits and are managed under recovery plans. For these stocks Total Allowable Catches (TAC’s) are generally low and quotas are accompanied by a broad variety of technical measures influencing the fishing patterns. Consequently, the input data to stock assessment models relying on catch statistics from the commercial fisheries is potentially biased and the perception of stock status may be incorrect. Egg production methods (EPM) provide a fishery independent alternative. Additionally, they provide better estimates of stock reproductive potential (SRP). Eastern Baltic cod (Gadus morhua callarias L.) has severely declined throughout the 2nd half of the 1980s and 1st half of the 1990s due to climate-driven adverse hydrographic conditions and high fishing intensity. Since 2007 the stock is managed under a long-term management plan and showed signs of recovery in most recent years. Since 1986, egg surveys have been carried out regularly in the Bornholm Basin, the most important spawning area of Eastern Baltic cod since mid-1980s. In the present paper the robustness of EPM towards simplification of spawning parameters and towards reduction of the number of egg surveys is tested applying three different methods requiring different numbers of egg surveys. We applied the annual egg production method (AEPM) requiring full egg survey coverage of the spawning season to estimate cod abundances in the Bornholm Basin. In addition, the daily fecundity reduction method (DFRM) and the daily egg production method (DEPM) were tested, the latter two methods requiring only single egg surveys, but require more complex reproduction input parameters. All three methods provided a comparable result, which was also expected as many spawning parameters were derived from the same underlying data sets. In a sensitivity analysis several input parameters were varied simultaneously up to 20% in both directions. EPM were especially sensitive towards changes in proportions of mature females ...